2018
DOI: 10.1002/jcb.27529
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of d‐amino acid oxidase mutations in amyotrophic lateral sclerosis

Abstract: Missense mutations in the coding region of d-amino acid oxidase (DAO) have been found in patients suffering from amyotrophic lateral sclerosis (ALS). Mutations primarily impair the enzymatic activity of DAO and cause neurodegeneration due to an abnormal accumulation of d-serine in the spinal cord. However, the structural and dynamic changes that lead to impaired enzymatic activity are not fully understood. We present here extensive molecular dynamics simulations of wild-type, and all reported ALS-associated DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…Our integrated study including MD simulations and in silico approaches reveal that certain structural and dynamic attributes corresponding to the active site residues, an active site loop comprising residues 216–228 and binding with cofactor FAD, contribute to the plausible loss of enzymatic activity, thus likely to be predisposing the individuals carrying these variations to ALS. This report and our earlier study 23 , employing MD simulations and other informatics-based analyses clearly demonstrate that certain Project MinE based rare DAAO variants are also loss-of-function type and could cause ALS through an unusual deposition of D-serine in the spinal cord.
Figure 1 Graphic representation of human D-amino acid oxidase showing its functional sites and rare DAAO variants.
…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Our integrated study including MD simulations and in silico approaches reveal that certain structural and dynamic attributes corresponding to the active site residues, an active site loop comprising residues 216–228 and binding with cofactor FAD, contribute to the plausible loss of enzymatic activity, thus likely to be predisposing the individuals carrying these variations to ALS. This report and our earlier study 23 , employing MD simulations and other informatics-based analyses clearly demonstrate that certain Project MinE based rare DAAO variants are also loss-of-function type and could cause ALS through an unusual deposition of D-serine in the spinal cord.
Figure 1 Graphic representation of human D-amino acid oxidase showing its functional sites and rare DAAO variants.
…”
Section: Introductionsupporting
confidence: 62%
“…First, only the missense variants with rare variant burden of 0.5% were extracted and variants for which the functional mechanisms are not known were selected for our study. Out of a total of 20 variants (V5A, R38H, D46N, H78Y, F90V, P103L, R115W, P119L, R199W, R199Q, L215F, P268S, R279Q, R283Q, R286C, L329F, G331E, S340F, S345F and S345C), the R38H, R199W and R199Q variants were not included in this study because they were previously studied by us and others 13,14,23 . Further, variants S345F and S345C were excluded because the crystal structure of WT-DAAO (PDB ID: 2E49) contains residues until Ser340 only.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MD simulation provides a complete understanding of the phenotypic expressions of mutations by generating detailed information on conformational and structural consequences at a reasonable quality and adequate time scale 52 . Several recent studies have investigated the correlation between experimental studies and MDS analysis, and have suggested MDS studies are helpful for uncovering underlying mutation-associated disease mechanisms, especially in the context of neurodegeneration 40,[53][54][55][56][57] . It has been suggested in previous MD simulation studies that R47H is responsible for loop distortions in TREM2 58 and to induce flexibility, particularly in CDR2 loops 59 .…”
Section: Mechanistic Insights Into Conformational Remodeling Intra-rmentioning
confidence: 99%
“…The structures and functions of DAAO have received intense attention in recent years due to its versatility. [26][27][28][29][30] In 1995, Schell et al discovered that D-Ser was localized principally within glial cells. Specifically, they found that type-2 astrocytes, which were cultured from cerebral cortex, expressed particularly high levels of D-Ser.…”
Section: Natural Occurrence and Biological Functions Of D-amino Acidsmentioning
confidence: 99%